US-UK counter-terrorism after 9/11 a qualitative approach - Tembo, Edgar B. (Contemporary terrorism studies, 2014)
"This book provides a qualitative analysis of post 9/11 counter-terrorism strategy undertaken by the UK and USA.Since 9/11 both the UK and the USA have significantly revamped their counter-terrorism approaches. The approaches apply, to varying degrees three key policy instruments intelligence, law enforcement and military force. However the success or failure of these counter-terrorism strategies has never been satisfactorily validated. Analysts and policymakers alike have assumed success due to the inability of terrorists to conduct 7/7 and 9/11 respectively, scale attacks upon each state. This assumption has existed despite the fact that it fundamentally underestimates the impact of transnational terrorism.This volume provides an in-depth qualitative assessment of the three primary policy instruments implemented to counter the transnational threat of terrorism during the period 2001-2011 an approach somewhat neglected by the current body of literature which focuses on a purely quantitative methodology. Drawing upon previously unpublished data collected from interviews with policymakers, specialists and academics, US-UK Counter-Terrorism after 9/11 fills this lacuna by ascertaining and analysing both the UKs and USAs counter-terrorism strategies and developing a holistic approach to understanding these strategies.This book will be of interest to students of terrorism and counter-terrorism studies, security studies and IR in general. "-- Provided by publisher